1994
DOI: 10.1042/bj3020291
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two acidic residues involved in the catalysis of xylanase A from Streptomyces lividans

Abstract: On the basis of similarities between known xylanase sequences of the F family, three invariant acidic residues of xylanase A from Streptomyces lividans were investigated. Site-directed-mutagenesis experiments were carried out in Escherichia coli after engineering the xylanase A gene to allow its expression. Replacement of Glu-128 or Glu-236 by their isosteric form (Gln) completely abolished enzyme activity with xylan and p-nitrophenyl beta-D-cellobioside, indicating that the two substrates are hydrolysed at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…It is possible that xylan forms such strong interactions with other residues within the active site cleft that removal of the C-2-O/E43 interaction does not alter the position of the substrate within the enzyme. This hypothesis is in agreement with Moreau et al (29), who also demonstrated that a mutation within XYLASL, D124E, had a much greater effect on the affinity of the enzyme for PNPC compared with xylan.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is possible that xylan forms such strong interactions with other residues within the active site cleft that removal of the C-2-O/E43 interaction does not alter the position of the substrate within the enzyme. This hypothesis is in agreement with Moreau et al (29), who also demonstrated that a mutation within XYLASL, D124E, had a much greater effect on the affinity of the enzyme for PNPC compared with xylan.…”
Section: Discussionsupporting
confidence: 82%
“…It remains to be established whether Cex or XYLA represents the best paradigm for family 10 xylanases. However, the observation that XYLASL has a K m for PNPC intermediate between XYLA and Cex (29) suggests that family 10 enzymes will exhibit a range of different activities for the aryl ␤-glycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of E-128 or E-236 by isosteric glutamine completely abolished its enzymatic activity (Moreau et al 1994). Furthermore, Henrissat identified the sequence around E-236 of XlnA 32kD as the glycosyl hydrolase family-10 active site (Henrissat 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis of the equivalent carboxylates also showed loss of catalytic activity in Streptomyces lividans xylanase A 21 (XAS) and XYLA. 4,22 Family 10 belongs in turn to the 4/7 superfamily 23 (or clan GH-A 24 ) of TIM-barrels, which includes glycosyl hydrolases with diverse specificities but a common structural framework, conserved catalytic residues, and common evolutionary origin.…”
Section: Xylanasesmentioning
confidence: 95%